Signatures of different carbon bonds in graphene oxide from soft x‐ray reflectometry. (14th July 2015) - Wahab, Hud; Xu, Guangyuan; Jansing, Christine; Gilbert, Markus; Tesch, Marc F.; Jin, Jianyong; Mertins, Hans‐Christoph; Timmers, Heiko
<x xml:space="preserve">Abstract</x> In graphene oxide, the graphite lattice is intercalated with oxygen groups that bond to carbon atoms. These groups have a bearing on the possibility of using graphene oxide as a precursor to make graphene. The nature of carbon bonds in graphene oxide has been characterized with soft x‐ray reflection spectroscopy across the carbon K‐edge. Results distinguish graphene oxide synthesized with Hummers' method from that made using a method suggested by Tour. The observed spectra are consistent with those from near‐edge x‐ray absorption fine structure (NEXAFS) measurements. In particular, the expected carbon K‐edge resonances associated with excitations into molecular π*‐ and σ*‐states of CC bonds can be identified. Importantly, the greater oxidation efficiency of the method by Tour may be the reason for the observation of additional resonances that have been assigned to carbon bonding with molecular groups containing oxygen. The additional resonances have been interpreted as the excitations of carbon 1 s electrons into the carbonyl π*(CO) orbital in the molecular group –COOH and into the hydroxyl π*(COH) orbital, respectively. Copyright © 2015 John Wiley & Sons, Ltd.